2008
DOI: 10.1111/j.1442-9993.2004.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of vegetation and vertebrate fauna to 23 years of fire exclusion in a tropical Eucalyptus open forest. Northern Territory, Australia

Abstract: This opportunistic study compares the vegetation, fuel loads and vertebrate fauna of part of a 120‐ha block of tropical open forest protected from fire for 23 years, and an adjacent block burnt annually over this period. Total fuel loads did not differ significantly between the unburnt and annually burnt sites, but their composition was markedly different, with far less grassy fuel, but far more litter fuel, in the unburnt block. There were major differences between treatments in the composition of trees and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
156
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(169 citation statements)
references
References 44 publications
11
156
2
Order By: Relevance
“…Rossatto et al (2009) found that forest species grew (diameter growth) faster than did savanna species in cerrado, but their fire response ) suggests that forest species did not acquire thicker bark than savanna species. Similarly, although in Australia forest species grow faster than savanna species (Prior et al 2004) they are excluded from savannas by fire impacts (Wilson and Bowman 1994, Russell-Smith et al 2003, Woinarski et al 2004). More importantly in our study of a typical fire-prone Australian savanna, height-response or fast height growth per se did not explain the success of the eucalypts; by simply growing taller than the flame height, trees did not necessarily escape the effects of fire (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Rossatto et al (2009) found that forest species grew (diameter growth) faster than did savanna species in cerrado, but their fire response ) suggests that forest species did not acquire thicker bark than savanna species. Similarly, although in Australia forest species grow faster than savanna species (Prior et al 2004) they are excluded from savannas by fire impacts (Wilson and Bowman 1994, Russell-Smith et al 2003, Woinarski et al 2004). More importantly in our study of a typical fire-prone Australian savanna, height-response or fast height growth per se did not explain the success of the eucalypts; by simply growing taller than the flame height, trees did not necessarily escape the effects of fire (cf.…”
Section: Discussionmentioning
confidence: 99%
“…There is less information on the effects of fire exclusion and the available information suggests the effects vary between systems (e.g. Lunt and Morgan 1999;Woinarski et al 2004;Gent and Morgan 2007). Short fire intervals (as experienced in frequent fires) are thought to result in the decline or disappearance of some species, most commonly obligate seeding shrubs, and the increase in other species with short maturation times, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing recognition that recurrent fire disturbance limits the dominance of trees and that without fire, the grass layer in mesic savannas is very much reduced and tree cover increases (Bond 2008, Bond et al 2005, Swaine et al 1992, Trapnell 1959, Woinarski et al 2004. Saplings are thought to be particularly vulnerable because stems in this size class are readily defoliated or killed by grass fires, yet are too large for their above-ground biomass to be quickly replaced from below-ground carbohydrate stores following top-kill, as happens for smaller stems (Hoffmann & Solbrig 2003).…”
Section: Introductionmentioning
confidence: 99%